Curve number hydrology : state of the practice - Hawkins, Richard H., 1934- (American Society of Civil Engineers, 2009)
The curve number (CN) method for estimating direct runoff response from rainstorms was developed to fill a technological niche in the 1950s. This book contains topics that include: an introduction to curve number hydrology; the curve number method; findings and developments; structure of the basic equation; and, soil moisture modeling.
Keywords: Runoff.; Rain and rainfall.; Hydraulic engineering.; Hydrology.; Water resources development.; Conservation of natural resources.; elektronické knihy; electronic books